MEDIA PEMBELAJARAN BAHASA ARAB BERBASIS DIGITAL 4.0 (KAHOOT DAN SOCRATIVE) PADA SEKOLAH DASAR - Fashi Hatul Lisaniyah; Ummidlatus Salamah (PREMIERE : Journal of Islamic Elementary Education, 2020)
This study aims to describe Arabic language learning media era 4.0 from conceptual and actual aspects and focuses on media learning Arabic language specifically elementary school (Junior hight school). The approach of this study is (library research) by discussing literatures that discuss arabic language learning media. Conclusion of this study is innovation of learning, especially in Arabic language lessons, is something important and must be owned or done by arabic teachers. This is because learning will be more enjoyable and meaningful for students. With kahoot and socrative media, it is expected to encourage students to be more enthusiastic and happy to learn Arabic. As a teacher who interacts with students every day, it is not wrong to constantly innovate in learning. Entering this 4.0 era, teachers are required to keep trying to find, explore and find breakthroughs, approaches, methods and learning media is one of the supporting new media that will be fresh and enlightening. This article describes the media of Arabic language learning for the basic level, covering the learning media of Kahoot and Socrative. The more creative and innovative a teacher is in using learning media will make it easier to deliver Arabic lessons, the easier it is for students to receive Arabic lessons. This is a major factor in the success of MI-level Arabic lessons.